RESPONSE OF BIOMASS AND PHOTOSYNTHESIS IN NON-HEADING CHINESE CABBAGE TO EXCESS COPPER - X. H. Wang; Y. P. Song; J. Ren; T. K. Liu; X. L. Hou; Y. Li (Journal of Animal and Plant Sciences, 2013)
Non-heading Chinese cabbage is one of the main vegetables in Asia, especially in China. To analyze the tolerance of non-heading Chinese cabbage to copper (Cu) stress, 10μM, 100μM and 1mM copper were used to treat two cultivars of ‘Wutacai’ as well as ‘Erqing’ and then photosynthesis, chlorophyll fluorescence parameters, biomass and chlorophyll content were investigated. In our study, 1mM copper significantly inhibited the photosynthesis and plant growth of both two cultivars. While at 100μM copper, the growth inhibition was just found in ‘Erqing’, not in ‘Wutacai’. The inhibition of copper on the photosynthesis was not only by stomatal factors but also by non-stomatal factors. Copper stress caused damage of photosystem resulting in reduction of PSII efficiency while non-photochemical-quenching parameter NPQ increased. Besides, at low concentration with 10μM, copper promoted the photosynthesis and plant growth. Therefore, the copper tolerance of non-heading Chinese cabbage was dependent on the genotype, and the plant growth inhibition under copper stress was due to the damage of photosystem. Our results will provide a theoretical basis for a further study on non-heading Chinese cabbage tolerance to copper and will be helpful for the production of non-heading Chinese cabbage in heavy metals contaminated areas.
Keywords: Copper stress; biomass; photosynthesis; chlorophyll fluorescence parameters; non-heading Chinese cabbage